Impaired brain endocannabinoid tone in the activity‐based model of anorexia nervosa. Issue 11 (27th August 2019) - Collu, Roberto; Scherma, Maria; Piscitelli, Fabiana; Giunti, Elisa; Satta, Valentina; Castelli, M. Paola; Verde, Roberta; Fratta, Walter; Bisogno, Tiziana; Fadda, Paola
Abstract: Objective: Despite the growing knowledge on the functional relationship between an altered endocannabinoid (eCB) system and development of anorexia nervosa (AN), to date no studies have investigated the central eCB tone in the activity‐based anorexia (ABA) model that reproduces key aspects of human AN. Method: We measured levels of two major eCBs, anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG), those of two eCB‐related lipids, oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), and the cannabinoid type‐1 receptor (CB1R) density in the brain of female ABA rats, focusing on areas involved in homeostatic and rewarding‐related regulation of feeding behavior (i.e., prefrontal cortex, nucleus accumbens, caudato putamen, amygdala, hippocampus and hypothalamus). Analysis was carried out also at the end of recovery from the ABA condition. Results: At the end of the ABA induction phase, 2‐AG was significantly decreased in ABA rats in different brain areas but not in the caudato putamen. No changes were detected in AEA levels in any region, whereas the levels of OEA and PEA were decreased exclusively in the hippocampus and hypothalamus. Furthermore, CB1R density was decreased in the dentate gyrus of hippocampus and in the lateral hypothalamus. After recovery, both 2‐AG levels and CB1R density were partially normalized in some areas. In contrast, AEA levels became markedly reduced in all the analyzed areas. Discussion: These data demonstrate an altered brain eCB tone in ABA rats, further supporting the involvement of an impaired eCB system in AN pathophysiology that may contribute to the maintenance of some symptomatic aspects of the disease.